Problem Penelitian Surat Setoran Pajak Daerah (SSPD) Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) Kota Yogyakarta Ditinjau dari Teori Organisasi - Halida Evy Hermaya; Arvie Johan (Notaire, 2026)
This study aims to examine and analyze the impediments encountered in the verification process of the SSPD BPHTB in Yogyakarta City, viewed through the lens of organizational theory, alongside projecting strategies to mitigate such impediments. This research employs an empirical legal research methodology. The study utilizes primary data acquired through interviews with key informants, as well as secondary data derived from library research. Data analysis was conducted using a qualitative method, entailing the systematic processing of primary and secondary data, followed by drawing conclusions through deductive reasoning. The findings conclude that, first, based on organizational theory, the execution of SSPD BPHTB verification in Yogyakarta City continues to face a number of impediments concerning structural, behavioral, and organizational dynamics aspects. Second, projections to minimize these obstacles include delineating specific work units dedicated to handling PBB-P2 and BPHTB; capacity building; establishing PBG data integration with the Dinas PUPKP; collaborating with third parties for PBB-P2 data updating; and digitalizing BPHTB service processes, including the PBB-P2 Validation Check at the BPKAD of Yogyakarta City. Furthermore, it is imperative to conduct dissemination regarding the procedure for completing PBB-P2 Validation Check documents to the PPAT in Yogyakarta City, as well as raising public awareness regarding the importance of reporting the SPOP and LSPOP upon the occurrence of changes to the tax object.